Aerospace series. Connector, electrical and optical, rectangular, modular, rectangular inserts, operating temperature 175 °C (or 125 °C) continuous. Size 3 plug for rack and panel applications, class C and D. Product standard Part 131, (31st January 2016) - British Standards Institution,
No abstract available